Cerebral vasculitis in severe Kawasaki disease: early detection by magnetic resonance imaging and good outcome after intensive treatment - GITIAUX, CYRIL; KOSSOROTOFF, MANOELLE; BERGOUNIOUX, JEAN; ADJADJ, ELIAS; LESAGE, FABRICE; BODDAERT, NATHALIE; HULLY, MARIE; BRUGEL, DOMINIQUE; DESGUERRE, ISABELLE; BADER‐MEUNIER, BRIGITTE (Developmental medicine and child neurology, 2012)
Kawasaki disease is an acute vasculitis, that has a classic complication of acquired coronary artery aneurysm. Severe forms with multi‐organ involvement or neurological dysfunction are rare. Cerebral vascular involvement has been related to large‐vessel injury or cardioembolism, leading to focal brain infarction. A 4‐year‐old female presented with unusual, rapidly catastrophic Kawasaki disease with refractory shock, acute renal failure, and coma, requiring intensive haemodynamic management. The observation of diffuse micro‐haemorrhages (T2*‐weighted sequence) associated with white matter injury on brain magnetic resonance imaging (MRI) pointed towards lesions of the medium/small blood vessels. Cerebral vasculitis was suspected and the immunosuppressive treatment was increased Subsequently, the patient’s recovery was rapid. On follow‐up severe, bilateral vitritis was evident and surgery improved visual outcome. Early recognition of severe or unusual forms of Kawasaki disease could lead to more favourable outcome using appropriate treatment strategies. Diffuse cerebral micro‐haemorrhages on T2* brain MRI sequences might be a key sign for the diagnosis of medium or small cerebral vessel involvement.